Red Cell Distribution Width to Platelet Rasio is not inferior than Aspartate Aminotransferase to Platelet Ratio Indeks Score in Predicting Liver Fibrosis in Chronic Hepatitis B Patients at Sanglah General Hospital Denpasar - Jemi Tubung; I Ketut Mariadi; IDN Wibawa (The Indonesian Society for Digestive Endoscopy, 2018)
Background: Red cell distribution width to platelet ratio (RPR) is known to be associated with a degree of liver fibrosis in patients with hepatitis B. This study aims to compare the under curve area, sensitivity, specificity, positive predictive value, and negative predictive value between RPR and aspartate aminotransferase to platelet ratio index (APRI) score with degree of fibrosis.Method: This study is a retrospective study, data taken from medical records of all chronic hepatitis B patients examined by Fibroscan at Sanglah General Hospital Denpasar, Bali from January 2016 to February 2018.Results: Ninety eight patients with chronic hepatitis B, 81 patients were recovered after exclusion of patients with chronic kidney disease, malignancy, and dengue haemorrhagic fever (DHF). In receiver operating characteristic (ROC) analysis, obtained area under the ROC curve (AUC) at RPR of 0.816, and at APRI score 0.797. In RPR with cut off 0.066 the sensitivity was 76.9%, specificity 78.6%, PPV 79.5%, NPV 73.8%. While APRI score with cut off 0.85 got 69.2% sensitivity, specificity 76.2%, PPV 73.0%, and NPV 72.7%. According to Kappa test, we found kappa coefficient 0.653 (p 0.05).Conclusion: In predicting severe liver fibrosis in chronic hepatitis B patients, RPR is not inferior than APRI score, and may be used as a diagnostic marker, with 65.3% conformity.